Aristotelean Virtue and the Interpersonal Aspect of Ethical Character - Merritt, Maria (Journal of moral philosophy, 2009)
Abstract I examine the Aristotelean conception of virtuous character as firm and unchangeable, a normative ideal endorsed in the currently influential, broadly Aristotelean school of thought known as 'virtue ethics'. Drawing on central concepts of Aristotle's Nicomachean Ethics, I offer an account of how this ideal is supposed to be realized psychologically. I then consider present-day empirical findings about relevant psychological processes, with special attention to interpersonal processes. The empirical evidence suggests that over time, the same interpersonal processes that sometimes help to sustain character may also disrupt it, even among agents who have the right values in principle. Fortunately, the evidence also suggests some remedial measures. An important philosophical measure, I conclude, is for advocates of virtue ethics to address agents' psychological need for a systematic decision procedure that will focus attention primarily on substantive ethical considerations, rather than characterological assessment.